The ischemic preconditioning and postconditioning effect on the intestinal mucosa of rats undergoing mesenteric ischemia/reperfusion procedure - Santos,Carlos Henrique Marques dos (2008)
PURPOSE: To evaluate the effect of the ischemic preconditioning and the ischemic postconditioning over the tissue injury in the intestinal mucosa of rats undergoing the procedure of mesenteric ischemia and reperfusion. METHODS: Thirty Wistar rats were studied, divided in three groups: group A, undergoing mesenteric ischemia (30 minutes) and reperfusion (60 minutes); group B, mesenteric ischemia and reperfusion preceded by ischemic preconditioning; group C, mesenteric ischemia and reperfusion and, before the beginning of reperfusion, the ischemic postconditioning was performed. At the end, a segment of the small intestine was dissected for histological analysis. The results were evaluated using the CHIU et al.6 classification followed by the statistic treatment. RESULTS: The mean values of the tissue injury levels were: group A, 3.5; group B, 1.2; and group C, 1. The difference between the result of group A with the results of groups B and C was considered statistically significant (p < 0,05). CONCLUSION: The ischemic preconditioning and postconditioning are able to minimize the tissue injury in the intestines of rats that underwent the procedure of mesenteric ischemia and reperfusion.